Including the Oft-Forgotten: The Necessity of Including Women and Indigenous Peoples in Nature-Based Solution Research - Gaspers, Anne; Oftebro, Thea Lurås; Cowan, Emily (Frontiers in Climate, 2022)
Nature-based Solutions (NbS) are a priority area for the European Commission. The European Union (EU) will fund projects on NbS under Horizon Europe, the EU’s framework programme for research and innovation (2021-2027). We argue the Commission should fund more projects that actively include local communities in the development and implementation of NbS. Specifically, the Commission should fund projects that include two oft-forgotten stakeholder groups: women and indigenous peoples. The literature demonstrates that success of NbS is dependent on the inclusion of a variety of stakeholders and that indigenous peoples and women and girls are critically important stakeholders. As the inclusion of these stakeholders is vital to the success of NbS, funding projects that specifically include these stakeholders will help the EU to achieve two important policy goals: the goal to provide evidence for NbS and the goal to advance the development, uptake and upscale of NbS.